PKM PENINGKATAN PENGETAHUAN DIGITALISASI MARKETING, AKUNTANSI DAN PERPAJAKAN KELOMPOK PENENUN DIAN’S TENUN & SONGKET KLUNGKUNG - Cokorda Krisna Yudha; Cok Istri Ratna Sari Dewi; Ida Bagus Gde Indra Wedhana Purba (Universitas Kadiri, 2021)
Klungkung Regency is one of the smallest regencies in Bali Province, but Klungkung Regency is famous for the handicrafts from each village. The emergence of the covid 19 outbreak, the number of craftsmen is decreasing and making craftsmen turn to business. It is necessary to improve the process of tax reporting, preparation of financial reports and marketing strategies for the weaving industry in Gelgel Village, Klungkung Regency. Providing material. Accounting and Marketing Mix strategies related to the benefits of marketing strategies in increasing sales turnover. The initial activity to be carried out is to build coordination with the manager of Dian Rumah Songket. This coordination is very important so that when implementing synergies activities can be achieved, the form of this community service program is the first training in preparing financial reports according to standards. Then after being given information about financial reporting, it is followed by providing materials related to digitalization Marketing. The target audience has an understanding of Tax Reporting, Preparation of Financial Reports for business financial conditions, Standard Financial Reports and Marketing Strategies in the Digital Era of Dians weaving and Songket businesses in Gelgel Klungkung village.